Self-harm emergency department visits in Canada during the COVID-19 pandemic: evidence from a sentinel surveillance system - Shikha Saxena; Li Liu; Nathaniel Pollock; Steven R. McFaull (BMC, 2023)
Abstract Background Self-harm is a leading cause of morbidity and mortality globally, though the prevalence tends to be highest among adolescents. As an indicator in suicide surveillance, the incidence of self-harm is useful because it is sensitive to social, environmental, and economic conditions. During the COVID-19 pandemic, the epidemiology of self-harm has varied across contexts. This study aims to investigate the changes in self-harm emergency department visits in 2020 compared to a pre-pandemic period in 2018-2019. Methods Self-harm emergency department visits were extracted from the Canadian Hospitals Injury Reporting and Prevention Program database from 2018 to 2020. We compared the data in 2020 with the pre-pandemic baseline in 2018-2019. We examined the changes in volume, the percentages of self-harm cases among all intentional injuries by sex, age group, and the proportions of self-harm cases by method of injury. We also quantified the time trends of the percentages of self-harm cases among all intentional injuries using Joinpoint regression. Results The overall volume of emergency visits related to self-harm was higher in 2020 during weeks 24-51 compared to the average volumes for the same weeks of 2018-2019. Percentage of self-harm among all intentional injury emergency department visits was significantly higher by 6.1% among females (p < 0.05) and by 5.3% among males in 2020 than in 2018-2019 (p < 0.05). The 11-to-18-year age group showed an increase in the percentage of self-harm among all intentional injury emergency department visits by 7.4% in 2020 when compared to 2018-2019. Time trend analyses showed that the percentages of self-harm among all intentional injury emergency department visits were higher during weeks 4-52 in 2020 than in 2018-2019, for both males and females. Conclusions The percentage of emergency department visits related to self-harm among all intentional injury visits were higher during 2020 than in 2018-2019. These results underscore the importance of continued surveillance of self-harm in Canada to better understand the sociodemographic factors affecting self-harm and to inform the prevention strategies and policies.